From Christ to Confucius : German Missionaries, Chinese Christians, and the Globalization of Christianity, 1860-1950 - Wu, Albert Monshan (New Haven, CT : Yale University Press, 2016)
A bold and original study of German missionaries in China, who catalyzed a revolution in thinking among European Christians about the nature of Christianity itself In this accessibly written and empirically based study, Albert Wu documents how German missionaries chastened by their failure to convert Chinese people to Christianity reconsidered their attitudes toward Chinese culture and Confucianism. In time, their increased openness catalyzed a revolution in thinking among European Christians about the nature of Christianity itself. At a moment when Europe s Christian population is falling behind those of South America and Africa, Wu s provocative analysis sheds light on the roots of Christianity s global shift.
Frontmatter -- Contents -- Abbreviations -- introduction: Perceptions of Failure -- Chapter One: The Missionary Impulse -- Chapter Two: Responding to Failure -- Chapter Three: Missionary Optimism -- Chapter Four: A Fractured Landscape -- Chapter Five: Order Out of Chaos -- Chapter Six: Falling in Love with Confucius -- Chapter Seven: Unfulfilled Promises -- Chapter Eight: Fruits of the Spirit -- Conclusion: Failure and Success -- Notes -- Glossary -- Bibliography -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Sep 2019)
Keywords: Confucianism; Missionaries -- China -- History; RELIGION / Christian Church / History